1994
DOI: 10.1042/bj3040715
|View full text |Cite
|
Sign up to set email alerts
|

Binding of high-molecular-mass kininogen to the Apple 1 domain of factor XI is mediated in part by Val64 and Ile77

Abstract: We have previously demonstrated the presence of a binding site for high-molecular-mass kininogen (HK), spanning residues Val59-Lys83, in the first Apple (A1) domain in the heavy-chain region of factor XI. We have now prepared conformationally constrained synthetic peptides and recombinant A1 domain (rA1) constructs to identify the specific amino acid residues that constitute the HK-binding site. Expression of the A1 domain (Glu1-Ser90) was achieved in a bacterial expression system following PCR amplification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Therefore, the binding sites for HK and thrombin in the A1 domain, although contiguous, are apparently separate and distinct. Another experiment that supports this conclusion is that after reduction and alkylation, the rA1 domain (Glu 1 -Ser 90 ) retains the capacity to inhibit FXI binding to HK (IC 50 ϳ10 Ϫ6 M) (19,20,37), whereas it is unable to inhibit thrombincatalyzed FXI activation (data not shown).…”
Section: -Ser 86mentioning
confidence: 84%
See 3 more Smart Citations
“…Therefore, the binding sites for HK and thrombin in the A1 domain, although contiguous, are apparently separate and distinct. Another experiment that supports this conclusion is that after reduction and alkylation, the rA1 domain (Glu 1 -Ser 90 ) retains the capacity to inhibit FXI binding to HK (IC 50 ϳ10 Ϫ6 M) (19,20,37), whereas it is unable to inhibit thrombincatalyzed FXI activation (data not shown).…”
Section: -Ser 86mentioning
confidence: 84%
“…Therefore, we examined the effects of mutations of these two residues on the capacity of the rA1 domain to inhibit thrombin-catalyzed FXI activation. We found that mutant rA1 domain constructs (Val 64 3 Ala and Ile 77 3 Ala), which have lost the capacity to inhibit FXI binding to HK (37), retain the full capacity of the rA1 domain (Glu ) to inhibit thrombin-catalyzed FXI activation (Fig. 2).…”
Section: -Ser 86mentioning
confidence: 90%
See 2 more Smart Citations
“…In a current model of FXI activation, the circulating FXI dimer is complexed with either HMWK (17)(18)(19) or prothrombin (18,20), both of which bind to the A1 domain of FXI (21).…”
mentioning
confidence: 99%